2017
DOI: 10.1002/acm2.12131
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of robust optimization plan with partial‐arc VMAT for photon volumetric‐modulated arc therapy: A phantom study

Abstract: This study investigated position dependence in planning target volume (PTV)‐based and robust optimization plans using full‐arc and partial‐arc volumetric modulated arc therapy (VMAT). The gantry angles at the periphery, intermediate, and center CTV positions were 181°–180° (full‐arc VMAT) and 181°–360° (partial‐arc VMAT). A PTV‐based optimization plan was defined by 5 mm margin expansion of the CTV to a PTV volume, on which the dose constraints were applied. The robust optimization plan consisted of a directly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 18 publications
0
10
0
Order By: Relevance
“…Robust optimization was initially introduced for intensity-modulated proton therapy (IMPT) to ensure adequate target dose coverage to account for position and proton range uncertainties [23]. It has been available for x-ray beam in radiation therapy treatment planning system recently [24]. A 4D robust optimization method was introduced by Liu et al to further reduce the impact of uncertainties including intra-fraction organ motion and shape changing to treat lung cancer [25].…”
Section: Methodsmentioning
confidence: 99%
“…Robust optimization was initially introduced for intensity-modulated proton therapy (IMPT) to ensure adequate target dose coverage to account for position and proton range uncertainties [23]. It has been available for x-ray beam in radiation therapy treatment planning system recently [24]. A 4D robust optimization method was introduced by Liu et al to further reduce the impact of uncertainties including intra-fraction organ motion and shape changing to treat lung cancer [25].…”
Section: Methodsmentioning
confidence: 99%
“…Similar observations were reported by Miura et al . [ 26 ] Their phantom based study in PTV, they showed that nonrobust volumetric-modulated arc therapy (VMAT), are less robust than robustly optimized CTV-based VMAT plans for set up uncertainties. Our study points out the need to consider robust optimization-based IMRT plans and also that robust evaluation should be performed before clinical selection of IMRT and proton plans.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies compared the robustness of CMRO and PTV-based optimization by shifting the planning CT without dose re-calculation, implicitly assuming dose invariance, which could lead to bias in favor of PTV-based optimization [5] or by systematic shifts with a dose recalculation could lead to bias in favor of CMRO [28]. By evaluating the dose on daily CBCTs, the EAGD accounts for geometrical variations and is very close to the actually given dose and not biased towards CMRO or PTV-based optimization.…”
Section: Discussionmentioning
confidence: 99%